Students' Perceptions Of Chatgpt AI As A Writing Tool For Senior High School Of English Learning - Wardhana, Nadine; Authar, Nailul; Saputri, Tyas; Sarkawi, Djuwari; Zaniar, Savira (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines secondary school students’ attitudes toward using ChatGPT as an educational tool for English writing. Since the development of artificial intelligence (AI), ChatGPT has increasingly been used to support writing skill development, particularly in idea generation, proofreading, vocabulary enrichment, and improving writing structure. In the context of English language learning, writing is often considered a challenging skill because students must organize ideas, apply grammar rules, choose appropriate vocabulary, and maintain coherence in their texts. Therefore, the presence of ChatGPT offers potential assistance for students who need immediate feedback and writing guidance. This research employed a qualitative method using semi-structured interviews as the main data collection technique. A total of 25 students were purposively selected based on their English proficiency level and computer skills. The data were analyzed through thematic analysis to identify students’ perceptions, experiences, and concerns regarding the use of ChatGPT in English writing activities. The findings revealed that ChatGPT provided several benefits for students. It helped them improve their writing skills by giving instant feedback on grammar, punctuation, sentence structure, and organization. Students also reported that ChatGPT supported vocabulary acquisition by introducing new words, expressions, and alternative sentence forms. In addition, the tool stimulated idea generation, especially when students experienced difficulty starting or developing their writing. However, the study also found several limitations. Some students expressed concern about becoming overly dependent on AI, while others noted that ChatGPT’s suggestions were not always accurate or suitable.